Crystallization and preliminary crystallographic analysis of the major capsid proteins VP16 and VP17 of bacteriophage P23-77. - Rissanen, I; Pawlowski, A; Harlos, K; Grimes, J; Stuart, D; Bamford, J (2012)
Members of the diverse double-β-barrel lineage of viruses are identified by the conserved structure of their major coat protein. New members of this lineage have been discovered based on structural analysis and we are interested in identifying relatives that utilize unusual versions of the double-β-barrel fold. One candidate for such studies is P23-77, an icosahedral dsDNA bacteriophage that infects the extremophile Thermus thermophilus. P23-77 has two major coat proteins, namely VP16 and VP17, of a size consistent with a single-β-barrel core fold. These previously unstudied proteins have now been successfully expressed as recombinant proteins, purified and crystallized using hanging-drop and sitting-drop vapour-diffusion methods. Crystals of coat proteins VP16 and VP17 have been obtained as well as of a putative complex. In addition, virus-derived material has been crystallized. Diffraction data have been collected to beyond 3 Å resolution for five crystal types and structure determinations are in progress.